From guidelines to bedside - insomnia treatment practices in South Korea: a nationwide cohort study - Moon, Daa Un; Piao, Zhaoyan; Lee, Do Hyun; Han, Euna (Frontiers in Psychiatry, 2024)
Background Insomnia is a prevalent disorder that impacts quality of life and leads to significant economic costs. Treatment includes both non-medication and pharmacological interventions, with international guidelines recommending cognitive behavioral therapy for insomnia (CBT-I) as the first-line treatment. Objective To describe current insomnia treatment practices in South Korea, focusing on pharmacological and non-medication treatments, and to identify gaps in guideline implementation. Methods This cohort study used data from the Korea National Health Insurance Service-National Sample Cohort (NHIS-NSC) from 2002 to 2019 and identified 18,003 patients newly diagnosed with insomnia between 2015 and 2019. This study analyzed treatment patterns and utilization rates. Results Of the 18,003 patients, 16,181 (89.9%) received pharmacological treatment, resulting in 35,638 prescriptions. Zolpidem (60%) and benzodiazepines (30-40%) were the most prescribed medications. Most patients were treated in clinics, with consistent dosages and increasing treatment lengths. Psychotherapy claims rose from 3.20% in 2015 to 9.14% in 2019, particularly in general hospitals (22.06% to 48.37%), but remained low in clinics (1.26% to 2.08%). Conclusion Pharmacological treatments dominate insomnia management in South Korea, with CBT-I being underutilized. Future efforts should focus on integrating non-pharmacological treatment into routine practice and exploring treatment risks and effectiveness based on patient demographics.